Hybrid plasmonic waveguide-assisted Metal–Insulator–Metal ring resonator for refractive index sensing. Issue 9 (21st May 2018) - Butt, M. A.; Khonina, S. N.; Kazanskiy, N. L.
Abstract: A highly sensitive refractive index sensor based on an integrated hybrid plasmonic waveguide (HPWG) and a Metal–Insulator–Metal (M–I–M) micro-ring resonator is presented. In our design, there are two slot-waveguide-based micro-rings that encircle a gold disc. The outer slot WG is formed by the combination of Silicon–Air–Gold ring and the inner slot-waveguide is formed by Gold ring–Air–Gold disc. The slot-waveguide rings provide an interaction length sufficient to accumulate a detectable wavelength shift. The transmission spectrum and electric field distribution of this sensor structure are simulated using Finite Element Method (FEM). The sensitivity of this micro-ring resonator is achieved at 800 nm/RIU which is about six times higher than that of the conventional Si ring with the same geometry. Our proposed sensor design has a potential to find further applications in biomedical science and nano-photonic circuits.